Metode Tahfiz pada Sekolah Islam Terpadu Muhammadiyah Langsa - Marhaban, Marhaban; Sanusi, Sanusi (Al Ashriyyah, 2023)
The modernization of the Muhammadiyah model of education, in particular the concept of "public school plus the Koran" has become the basis for the growth of modern Islamic schools in urban areas. Muhammadiyah of Langsa which organizes educational institutions based on the packaging of "public school plus the Koran". The formulation of the research problem is how the tahfidz method is at the Muhammadiyah Langsa Integrated Islamic School. The results showed that the tahfidz Al-Qur'an method used in learning at the Integrated Islamic School Muhammadiyah Langsa used the zidah and muraqaah methods and the halaqah (talaqqi) or jam'i method Modernisasi pendidikan model Muhammadiyah, khususnya konsep “sekolah umum plus Alquran” menjadi basis bagi pertumbuhan sekolah-sekolah Islam modern di perkotaan. Muhammadiyah Kota Langsa yang menyelenggarakan lembaga pendidikan berbasis dalam kemasan “sekolah umum plus Alquran”. Rumusan permasalahan penelitian ini adalah bagaimana metode tahfidz pada Sekolah Islam Terpadu Muhammadiyah Langsa. Hasil penelitian menunjukkan bahwa metode tahfidz Alquran yang dipergunakan dalam pembelajaran di Sekolah Islam Terpadu Muhammadiyah Langsa dengan menggunakan metode ziadah dan muraqaah serta metode halaqah (talaqqi) atau jam'i.